2022
DOI: 10.3390/gels8050313
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Novel P(OEGMA-co-MEO2MA) Microgels-Based Thermosensitive Hydrogel and Its Application in Three-Dimensional Cell Scaffold

Abstract: Thermosensitive hydrogel scaffolds have attracted particular attention in three-dimensional (3D) cell culture. It is very necessary to develop a type of thermosensitive hydrogel material with low shrinkage, and excellent biocompatibility and biodegradability. Here, five types of thermosensitive microgels with different volume phase transition temperature (VPTT) or particle sizes were first synthesized using 2-methyl-2-propenoic acid-2-(2-methoxyethoxy) ethyl ester (MEO2MA) and oligoethylene glycol methyl ether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…The use of hydrogels as scaffolds has made further progress recently. For example, Liu et al [ 110 ] prepared a thermosensitive hydrogel and used it for in situ embedding and three-dimensional culture of MCF-7 breast cancer cells. It was shown that this thermosensitive hydrogel can be used as a three-dimensional platform with high biocompatibility and easy functionalization, and has great potential in the biomedical field.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The use of hydrogels as scaffolds has made further progress recently. For example, Liu et al [ 110 ] prepared a thermosensitive hydrogel and used it for in situ embedding and three-dimensional culture of MCF-7 breast cancer cells. It was shown that this thermosensitive hydrogel can be used as a three-dimensional platform with high biocompatibility and easy functionalization, and has great potential in the biomedical field.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…As a result of this unique nanostructure, nanogels demonstrate a rapid response to changes in the environment. Accordingly, smart nanogels, also called stimuli-responsive nanogels, can be designed to achieve triggered drug release in response to various stimuli, such as light, ion-exchange, pH, and temperature [ 133 , 134 , 135 , 136 ]. The use of smart nanogels as a drug delivery system for anti-tumor phototherapy holds great promise, as evidenced by recent reports on thermosensitive nanogels [ 137 ], pH-sensitive nanogels [ 138 , 139 ], photosensitive nanogels [ 140 ], and redox-sensitive hydrogels [ 139 ].…”
Section: Hydrogelsmentioning
confidence: 99%
“…Farmasötik uygulamalarda genellikle sol-jel geçiş sıcaklığı için fizyolojik sıcaklık olan 37°C hedeflenmektedir [65]. Sıcaklık duyarlı hidrojel tasarımında kitozan, selüloz türevleri gibi doğal polimerler kullanılabilirken, sentetik kaynaklı olarak da poli N-izopropilakrilamid (pNiPAm), poli (etilen oksit)-b-poli (propilen oksit)-b-poli (etilen oksit) (PEO-PPO-PEO; Poloksamer), PEG-b-PCL, PEG-b-PLGA ve PEG-b-PLA gibi polimerler kullanılabilmektedir [66][67][68][69][70][71][72][73]. Lokal kanser uygulamalarında, in situ jel formülasyonlarında etkin maddenin çözelti formda çözünmüş olması, formülasyonun enjeksiyon sonrasında vücut sıcaklığındaki uygulama bölgesinde jel hale geçmesi, uzun süre stabilitesini koruyabilmesi ve enjektabl özelliğini koruması hedeflenmektedir [74].…”
Section: Sıcaklık Duyarlı Hidrojellerunclassified